Love, Amalia - Ada, Alma Flor 1938-; Zubizarreta, Gabriel M. (Atheneum Books for Young Readers, 2012)
Sixth-grader Amalia learns many important life-lessons while spending Friday afternoons with her beloved grandmother, and the teaching goes on even after Abuelita's sudden death as Amalia finds a way to connect with relatives and a friend who has moved away. -- Ages 8-12.